Remarks on the controllability of dynamics of propagation of cancer (Nonlinear Studies, 2024)
In this work, the investigation dedicated to the study of the control of the dynamics of the propagation of cancer using the math model suggested in article \cite{18} is provided. Here we show if the class of controlfunctions chosen at the beginning of the characteristics of the diseases then there exists such control operator by which influence can be cured or, at least, stop the growth of cancer